2014
DOI: 10.5946/ce.2014.47.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Therapeutic Impact of Rectal Retroflexion: A Prospective, Single-Blind Study Conducted in Three Centers

Abstract: Background/AimsNo clear data have been established and validated regarding whether rectal retroflexion has an important and therapeutic impact. The aim of the present study was to evaluate the diagnostic yield and therapeutic impact of rectal retroflexion compared with straight view examination.MethodsA prospective single-blind study was conducted. Consecutive patients evaluated between October 2011 and April 2012 were included.ResultsA total of 934 patients (542 women, 58%) were included. The mean age was 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…According to a report, important lesions are visible in the rectum by forward-view observations, 190 but there are some lesions that can be detected by retroflexion only. 191 There is a high possibility that retroflexion increases visibility of lesions in the anus and lower rectum. However, although rare, retroflexion carries a risk of intestinal perforation, 192,193 so it is desirable to avoid unreasonable procedure.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report, important lesions are visible in the rectum by forward-view observations, 190 but there are some lesions that can be detected by retroflexion only. 191 There is a high possibility that retroflexion increases visibility of lesions in the anus and lower rectum. However, although rare, retroflexion carries a risk of intestinal perforation, 192,193 so it is desirable to avoid unreasonable procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Endoscopy , Téllez-Ávila et al 11 conducted a prospective single-blind study in three centers to evaluate the diagnostic yield and therapeutic impact of RR compared with those of either digital rectal exploration or the straight view. They evaluated the therapeutic impact and diagnostic yield of RR during colonoscopy to elucidate whether RR can serve as a bridge over troubled water.…”
mentioning
confidence: 99%
“…For visualization of anal fissures, it is also essential to use the anoscope, which sometimes becomes impossible without sedation. A prospective, multicenter, blinded study by Tellez-Ávilla et al showed that RR during colonoscopy has limited effect and little impact on diagnosis and therapy 13 . Two prospective studies have shown that anoscopy was superior to RR in detection of hemorrhoids 1 2 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Rectal retroflexion (RR) is often used to evaluate hemorrhoids, but this technique has little sensitivity 1 5 . One study demonstrated that the gain related to the finding of lesions identified with RR was from 2 % to 8 % 13 . VA can determine the cause of bleeding if it is of anal origin.…”
Section: Discussionmentioning
confidence: 99%